Pengaruh Penggunaan Aspal Modifikasi Polimer Ethyl Vinyl Acetat (EVA) Terhadap Campuran Laston Asphalt Concrete Wearing Course (AC-WC): The Effect Of The Use Of Ethyl Vinyl Acetate (EVA) Modification Polymer On Mixed Asphalt Concrete Wearing Course (AC-WC) - Yosevina, Yosevina (Media Ilmiah Teknik Sipil, 2022)
Asphalt concrete (Laston) has a high level of flexibility so that the placement of such a layer directly above the wear layer (AC-WC) make this layer susceptible to damage is too high temperature and heavy traffic loads. In addition to these, as well as the damage is too high viscosity when asphalt mixing with aggregate due to the ineffectiveness of quality control in Asphalt Mixing Plant (AMP) so that the asphalt temperature is not controlled. This study is intended to take advantage of Ethylene Vinyl Acetate (EVA) as a polymer in a mixture of Asphalt Concrete – Wearing Course). Stages of materials testing carried out on three specimen to be used, ex Clereng aggregate, asphalt penetration pertamina 60/70, and modifier type of polymer Ethylene Vinyl Acetate (EVA). The test in laboratory with Marshall Test to acquire properties with a value of EVA modified aphalt content variation of 0% (Variation 1), 1% (Variation 2), 2% (Variation 3), 3% (Variation 4), and 4% (Variation 5). The result of Marshall Test showed that the addition variation 1 to variation 5 of EVA modified asphalt tend to increase Optimum Asphalt Content, stability value, and Marshall Quotient (MQ) value of AC-WC mixture. Generally, Asphalt Concrete-Wearing Course (AC-WC) mixtures with the addition of EVA modified asphalt gives the best result compared to AC-WC mixture without EVA modified asphalt